Seasonal blooms of Synechococcus in a temperate semi-enclosed bay: linking community succession to thermal and nutrient regimes - Ding, Xiaokun; Wu, Guannan; Zhang, Di; Yang, Long; Wang, Aobo; Li, Sheng; Gao, Li; Cui, Zhengguo; Jiang, Tao (Frontiers in Microbiology, 2025)
Synechococcus is a key picocyanobacterium in coastal ecosystems, yet its seasonal bloom dynamics and environmental responses remain unclear in temperate coastal seas. Here, we integrated flow cytometry and rpoC1 gene analysis to investigate its bloom development and community succession in Laizhou Bay, based on 3 years of 10 seasonal surveys and a year-long monthly observation at a fixed station. Synechococcus blooms reached their peak in summer (up to 106 cells mL−1), particularly in the southern part of the bay, with high abundances in autumn as well. Phycoerythrin-rich Synechococcus consistently dominated the community (>70%), especially during autumn blooms. Genetic analyses revealed that summer-autumn blooms harbored high clade diversity (S5.1 II, III, V, and VII), whereas winter and spring communities were simpler, dominated by S5.1 I and IV. Notably, S5.2. VIII gradually increased in relative abundance during bloom development, exceeding 50% in late autumn. Temperature emerged as the primary regulator of Synechococcus dynamics, with cell abundance increasing exponentially with rising temperature. Bloom events were consistently triggered above 26°C. In addition, external nutrient inputs, particularly riverine pulses accumulating from summer to autumn, contributed to Synechococcus bloom persistence and genetic diversification. This study provides valuable insights into the mechanisms regulating Synechococcus blooms and offers a methodological framework for understanding and predicting microbial community responses to the combined effects of climate change and anthropogenic disturbances in coastal ecosystems.